2017
DOI: 10.1038/s41598-017-10656-9
|View full text |Cite
|
Sign up to set email alerts
|

An intra-population analysis of the indris’ song dissimilarity in the light of genetic distance

Abstract: The increasing interest in the evolution of human language has led several fields of research to focus on primate vocal communication. The ‘singing primates’, which produce elaborated and complex sequences of vocalizations, are of particular interest for this topic. Indris (Indri indri) are the only singing lemurs and emit songs whose most distinctive portions are “descending phrases” consisting of 2-5 units. We examined how the structure of the indris’ phrases varied with genetic relatedness among individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 67 publications
8
54
1
Order By: Relevance
“…Indris ( Indri indri ; Gmelin, 1788) represent a distinctive species for studying vocal communication because of their rich repertoire (Maretti, Sorrentino, Finomana, Gamba, & Giacoma, 2010; Valente et al, 2019) and the impressive loud songs, unique among lemurs (Gamba et al, 2016; Torti et al, 2017), which can be heard at a distance up to 2 km (Pollock, 1986). Data on sound pressure levels revealed that the sound levels of the indri's song reached 110 dB (estimated at 0.50 m; Torti, pers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indris ( Indri indri ; Gmelin, 1788) represent a distinctive species for studying vocal communication because of their rich repertoire (Maretti, Sorrentino, Finomana, Gamba, & Giacoma, 2010; Valente et al, 2019) and the impressive loud songs, unique among lemurs (Gamba et al, 2016; Torti et al, 2017), which can be heard at a distance up to 2 km (Pollock, 1986). Data on sound pressure levels revealed that the sound levels of the indri's song reached 110 dB (estimated at 0.50 m; Torti, pers.…”
Section: Introductionmentioning
confidence: 99%
“…Females may use songs for mate attraction (Rogers et al, 2007), and they may even show a more elaborated song repertoire (Australian magpies; Gymnorhina tibice Brown & Farabaugh, 1991). Like Eastern whip birds and Australian magpies, indris are monogamous (Bonadonna et al, 2019; Torti et al, 2017), form groups that occupy nonoverlapping areas in the forest (Bonadonna et al, 2017), and use the songs to inform neighboring groups about the occupation of a territory and to actively defend resources during group encounters (Torti et al, 2013). Thus, we hypothesized that the female contribution to the song would be structurally different from that of males.…”
Section: Introductionmentioning
confidence: 99%
“…Main focus on behavioral and neurocognitive mechanisms 11 Focus on different explanatory levels, from genetics 10,53 to neurobiology and behavior 27…”
Section: Mechanismsmentioning
confidence: 99%
“…This historical focus on individual language capacities, partly due to a generativist tradition in language sciences, is rapidly changing . Unanswered questions regarding how individual communicative rhythms are shaped by group interactions and modulated by social behavior are starting to be addressed . The study of conversation and turn‐taking is taking center stage …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation